Tetragonal-phase zirconia / HA nano-array bioactive composite coating growing on zirconium alloy surface and preparation method of tetragonal-phase zirconia / HA nano-array bioactive composite coating
The calcium-stable tetragonal phase zirconia coating was prepared by using microarc oxidation method on the surface of Zr-2.5Nb alloy, and the HA nanorod array was grown in combination with hydrothermal reaction, which solved the problem of difficulty in surface modification of the alloy and significantly improved its osseous integration ability and biocompatibility.
Patent Information
- Application Number
- CN202411972913.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The prior art is difficult to prepare calcium-stable tetragonal zirconia and HA bioactive coatings on Zr-2.5Nb alloys, limiting the application of its orthopedic implants.
A porous calcium-stable tetragonal phase zirconia coating was generated on the surface of Zr-2.5Nb alloy by microarc oxidation, and a HA nanorod array bioactive coating was uniformly grown on its surface by hydrothermal reaction.
Effective modification on the surface of Zr-2.5Nb alloy is achieved, improving its osseous integration ability and mechanical properties, and enhancing biocompatibility and cellular response capabilities.
Smart Images

Figure CN119776949A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zirconium alloy surface treatment, and specifically relates to a tetragonal zirconium oxide / HA nano-array bioactive composite coating grown on the surface of a zirconium alloy and a method thereof. Background Art
[0002] Zirconium and zirconium alloys have shown broad application prospects in the field of biomedical implants (such as orthopedic and dental implants) due to their excellent mechanical properties and biocompatibility. However, like titanium alloys, zirconium alloys are bioinert materials and lack the ability to promote bone integration, which to some extent limits their application in orthopedic implants.
[0003] Zr-2.5Nb alloy is a commonly used zirconium alloy. In order to improve the bone integration ability of Zr-2.5Nb alloy, its surface modification is required.
[0004] Zirconia, as a bioinert ceramic, has high fracture strength and bending strength and is called ceramic steel. At room temperature, zirconia usually exists in a monoclinic phase, but by adding stabilizers, the stability of its tetragonal phase can be improved to form tetragonal zirconia that is stable at room temperature. Utilizing the phase change characteristics of tetragonal zirconia can improve the fracture toughness of the material, which is crucial to improving the long-term durability of implants. Calcium-stabilized tetragonal zirconia is prepared on the surface of zirconium alloy. Compared with the common yttrium-stabilized tetragonal zirconia ceramics, the former has finer grains, reaching the nanometer level, which is of positive significance for improving the mechanical properties of the material.
[0005] In addition, hydroxyapatite (HA) is a bioactive ceramic whose main component is Ca 10 (PO4)6(OH)2 is the main inorganic component of bones and teeth and is widely used as a bone substitute. HA not only has good biocompatibility, but also can effectively promote bone growth. After implantation in the body, it can form a chemical bond with the surrounding tissue at the interface. Its nanostructure can significantly enhance the function of mesenchymal stem cells in vitro, which is beneficial to promote the adhesion, proliferation and differentiation of osteoblasts, and further accelerate the bone integration process.
[0006] Therefore, the preparation of calcium-stabilized tetragonal zirconia and HA bioactive coatings on Zr-2.5Nb alloy can effectively achieve surface modification, thereby promoting its bone integration ability and improving the mechanical properties of the material. However, currently there are only reports on the preparation of tetragonal zirconia / HA bioactive dual coatings on titanium alloys by micro-arc oxidation and hydrothermal methods, but this method is not suitable for Zr-2.5Nb alloy. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a tetragonal zirconia / HA nanoarray bioactive composite coating and method grown on the surface of a zirconium alloy to solve the problem of preparing calcium-stabilized tetragonal zirconia and HA bioactive coatings on Zr-2.5Nb alloy. The surface modification of the Zr-2.5Nb alloy can be effectively achieved to achieve the purpose of promoting its bone integration ability and improving the mechanical properties of the material.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A tetragonal zirconia / HA nanoarray bioactive composite coating grown on the surface of a zirconium alloy, wherein the zirconium alloy is a Zr-2.5Nb alloy, the tetragonal zirconia coating covers the surface of the zirconium alloy, the tetragonal zirconia coating is a porous calcium-stabilized tetragonal zirconia coating containing Ca and P, the HA nanoarray bioactive coating grows uniformly on the surface of the tetragonal zirconia coating, the HA nanoarray bioactive coating is in the shape of a hexagonal prism, is nearly perpendicular to the porous structure surface, can significantly improve hydrophilicity, is beneficial to promoting the adhesion and proliferation of osteoblasts, and improves bone integration ability.
[0010] A method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface comprises the following steps:
[0011] S1, using Zr-2.5Nb alloy as anode, micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus in a pulse power constant voltage mode, the voltage is 300-500V, and a tetragonal ZrO2 coating containing Ca and P porous calcium stabilized is generated on the surface of the Zr-2.5Nb alloy to obtain a composite a;
[0012] S2, subjecting complex a to a first hydrothermal reaction in an alkaline solution at 60-140°C, and then subjecting it to a second hydrothermal reaction in an alkaline mixed solution containing calcium and phosphorus at 60-140°C, so that the HA nanoarray bioactive coating grows uniformly on the surface of the tetragonal zirconia coating to form a composite material, thereby completing the growth of the tetragonal zirconia / HA nanoarray bioactive composite coating on the surface of the zirconium alloy.
[0013] Preferably, the solvent of the alkaline electrolyte in S1 is deionized water, and the solutes are calcium sodium ethylenediaminetetraacetate, sodium dihydrogen phosphate and sodium hydroxide, the concentration of calcium sodium ethylenediaminetetraacetate is 0.01-0.2 mol / L, the concentration of sodium dihydrogen phosphate is 0.02-0.2 mol / L, and the concentration of sodium hydroxide is 0.05-0.25 mol / L.
[0014] Preferably, the micro-arc oxidation reaction described in S1 is carried out at a frequency of 50-200 Hz and a duty cycle of 7.5-26%.
[0015] Preferably, the micro-arc oxidation reaction described in S1 is carried out at a voltage of 300-500 V for 3-30 min.
[0016] Preferably, the alkaline solution described in S2 is a sodium hydroxide solution with a pH of 8-12.
[0017] Preferably, the first hydrothermal reaction described in S2 is carried out at 60-140° C. for 0.5-5 h.
[0018] Preferably, the second hydrothermal reaction described in S2 is carried out at 60-140° C. for 10-48 h.
[0019] Preferably, the solvent of the alkaline mixed solution described in S2 is deionized water, and the solutes are calcium sodium ethylenediaminetetraacetate, sodium dihydrogen phosphate and sodium hydroxide, the concentration of calcium sodium ethylenediaminetetraacetate is 0.2-0.5 mol / L, the concentration of sodium dihydrogen phosphate is 0.1-0.6 mol / L, and the concentration of sodium hydroxide makes the pH of the alkaline mixed solution 8-11.
[0020] Preferably, the Zr-2.5Nb alloy described in S1 is obtained by the following process: the initial Zr-2.5Nb alloy is polished with 400-mesh sandpaper, 800-mesh sandpaper and 1500-mesh sandpaper in sequence, then ultrasonically cleaned with acetone, deionized water and ethanol for 10-20 minutes respectively, and finally dried at 55-65° C. for 25-35 minutes;
[0021] The complex a obtained in S1 is rinsed with deionized water, then dried at 55-65°C for 25-35 minutes, and then subjected to the first hydrothermal reaction. After the first hydrothermal reaction, the complex b obtained is rinsed with deionized water, then dried at 55-65°C for 25-35 minutes, and then subjected to the second hydrothermal reaction. The composite material is rinsed with deionized water, then dried at 55-65°C for 25-35 minutes, thereby completing the growth of a tetragonal zirconia / HA nanoarray bioactive composite coating on the surface of the zirconium alloy.
[0022] Compared with the prior art, the present invention has the following beneficial technical effects:
[0023] The invention discloses a tetragonal zirconium oxide / HA nano-array bioactive composite coating grown on the surface of a zirconium alloy, wherein calcium-stabilized tetragonal zirconium oxide is generated on the surface of a Zr-2.5Nb alloy. 2+It is a strong stabilizer of the tetragonal phase, which enters the crystal lattice to form a substitutional solid solution, can be cooled quickly to avoid eutectoid decomposition, and the high-temperature tetragonal zirconia phase can be retained to room temperature. The stress-induced phase change of tetragonal zirconia can be used to improve the fracture toughness of the material; the porous zirconia coating is rich in calcium and phosphorus, which is conducive to the nucleation and growth of HA nanorods, and the zirconia grains reach the nanoscale, which improves the mechanical properties of the material; the bioactive coating HA nanorods uniformly covered on the porous zirconia structure are well crystallized, hexagonal, with a diameter of about 50-120nm, a spacing of about 60-300nm, and a height of 500-800nm, which is nearly perpendicular to the surface of the porous structure, can significantly improve hydrophilicity, which is conducive to promoting the adhesion and proliferation of osteoblasts and improving bone integration ability, and combines the dual functions of calcium-stabilized tetragonal zirconia and hydroxyapatite.
[0024] The present invention discloses a method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface. The method comprises the following steps: micro-arc oxidation is performed on the surface of the Zr-2.5Nb alloy using a pulse power supply constant voltage mode, spark discharge spots are generated in the micropores on the surface of the Zr-2.5Nb alloy, and then a rough tetragonal ZrO2 coating containing Ca and P porous calcium stabilization is generated on the alloy surface. The improvement of the surface roughness of the coating can improve osteogenesis and enhance the adhesion between the implant and the host bone. The higher the voltage, the more conducive it is to quickly generate a zirconium oxide coating with a large membrane pore size, a small number of pores and a high hardness. However, when the voltage is over 500V, local breakdown of the membrane layer is likely to occur, and the bonding strength is reduced. The calcium-stabilized tetragonal zirconium oxide is prepared by the micro-arc oxidation method, and its grains reach the nanometer level, which is conducive to improving the mechanical properties of the material. The solid solution of Ca in the zirconium oxide is favorable. The method further hydrothermally generates a HA bioactive coating; then, the first hydrothermal reaction is carried out in an alkaline solution at 60-140°C, and the calcium and phosphorus ions in the outermost layer of the porous calcium-stabilized tetragonal ZrO2 coating react with the alkaline solution through high-temperature thermal activation to form HA crystal nuclei on the surface of the ZrO2 coating. In the secondary hydrothermal reaction, the alkaline mixed solution provides calcium and phosphorus elements, and the crystal nuclei further grow to obtain a bioactive coating HA nanorod array uniformly grown on the surface of the porous calcium-stabilized tetragonal zirconia. When the hydrothermal temperature is lower than 60°C, it cannot provide sufficient power for the growth of HA, and the obtained HA nanorods are thinner. When the hydrothermal temperature is higher than 140°C, the obtained HA nanorods are unevenly distributed and the spacing increases. Thus, a firmly bonded porous calcium-stabilized tetragonal zirconia / HA bioactive composite coating is prepared on the surface of the Zr-2.5Nb alloy. The calcium-stabilized tetragonal zirconia / HA bioactive composite coating obtained by the present invention has good bonding strength, and the membrane-based bonding strength exceeds 20N. The nanorod array design is close to the nanofiber morphology of natural bones, has a bionic effect, can improve the biocompatibility of Zr-2.5Nb alloy, improve the cell response and bone conduction ability of implants, and promote the formation of new bone. It is of great significance in the direction of zirconium alloy orthopedic implants and hard tissue repair, effectively improves the biological activity of the zirconium alloy surface, promotes bone integration, and is expected to provide new ideas and methods for the research and development of biomedical implants, and promote the application prospects of zirconium alloys in the field of orthopedics.
[0025] Furthermore, the micro-arc oxidation alkaline electrolyte and hydrothermal solution prepared by the present invention have simple components and do not contain β-sodium glycerophosphate (β-GP), thereby reducing manufacturing costs and facilitating large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1a This is a SEM image of the surface morphology of the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 1 of the present invention.
[0027] Figure 1bThis is the surface EDS spectrum of the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 1 of the present invention.
[0028] Figure 2 This is a cross-sectional SEM image of the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 1 of the present invention.
[0029] Figure 3 This is the XRD diagram of the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 1 of the present invention.
[0030] Figure 4a This is a surface morphology SEM image of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method in Example 1 of the present invention.
[0031] Figure 4b This is the surface EDS energy spectrum of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method in Example 1 of the present invention.
[0032] Figure 4c This is a cross-sectional SEM image of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal methods in Example 1 of the present invention.
[0033] Figure 4d for Figure 4c Enlarged view of the white box area.
[0034] Figure 4e for Figure 4a Enlarged view of the white box area.
[0035] Figure 5 This is the XRD diagram of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method in Example 1 of the present invention.
[0036] Figure 6a Contact angle diagrams of the Zr-2.5Nb substrate, the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 1 of the present invention, and the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal methods.
[0037] Figure 6b Roughness map of Zr-2.5Nb matrix.
[0038] Figure 6c This is a roughness diagram of the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 1 of the present invention.
[0039] Figure 6d This is a roughness diagram of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method in Example 1 of the present invention.
[0040] Figure 7a This is a scratch morphology image of the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 1 of the present invention and a schematic diagram of the coating bonding force calculated based on the coating peeling position.
[0041] Figure 7b This is a scratch morphology image of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method in Example 1 of the present invention, and a schematic diagram of the coating bonding force calculated based on the coating peeling position.
[0042] Figure 8a This is a SEM image of the surface morphology of the calcium-stabilized zirconia coating obtained by micro-arc oxidation in Example 2 of the present invention.
[0043] Figure 8b This is a surface morphology SEM image of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method in Example 2 of the present invention.
[0044] Figure 8c for Figure 8b Enlarged view of the white box area.
[0045] Figure 9a This is a SEM image of the surface morphology of the calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation in Example 3 of the present invention.
[0046] Figure 9b This is a surface morphology SEM image of the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method in Example 3 of the present invention.
[0047] Fig.9c for Figure 9b Enlarged view of the white box area. DETAILED DESCRIPTION
[0048] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0049] The invention discloses a method for preparing a calcium-stabilized tetragonal zirconium oxide / HA nano-array bioactive coating on the surface of a zirconium alloy. The method utilizes a micro-arc oxidation method to prepare calcium-stabilized tetragonal zirconium oxide, wherein the grains thereof reach nanometer level, which is beneficial to improving the mechanical properties of the material. The solid solution of Ca element in zirconium oxide is beneficial to further hydrothermally generate the HA bioactive coating. The commonly used chemical reagent β-sodium glycerophosphate (β-GP) is abandoned, and sodium dihydrogen phosphate with lower cost is used as a substitute. The method specifically comprises the following steps:
[0050] Step 1: Use Zr-2.5Nb alloy as the anode and stainless steel as the cathode. Zr-2.5Nb alloy is an alloy material with high strength, high hardness, high corrosion resistance and high impact resistance. It is cylindrical in shape with a diameter of 14-40 mm. Use a pulse power constant voltage mode to carry out micro-arc oxidation reaction in an alkaline electrolyte containing calcium and phosphorus to generate spark discharge spots in the micropores on the surface of the Zr-2.5Nb alloy. Then, a tetragonal ZrO2 coating containing Ca and P porous calcium stabilized is generated on the surface of the alloy (zirconia dissolves Ca and P elements, and the ZrO2 coating is a ceramic film), which is beneficial to the growth of HA nanorods. Rinse with deionized water and dry for use. The electrolyte is composed of 0.01-0.2 mol / L calcium sodium ethylenediaminetetraacetate (EDTA-Ca), 0.02-0.2 mol / L sodium dihydrogen phosphate, and 0.05-0.25 mol / L sodium hydroxide. The solvent is deionized water, and the electrolyte temperature is maintained at 10-25°C. The voltage of the pulse power supply is 300-500V, the frequency is 50-200Hz, the duty cycle is 7.5-26%, and the micro-arc oxidation treatment time is 3-30min. In the electrolyte, the concentration of calcium sodium ethylenediaminetetraacetate (EDTA-Ca) and sodium dihydrogen phosphate increases, which is beneficial to increase the Ca and P content in the zirconium oxide coating. The increase in the micro-arc oxidation voltage is conducive to the rapid generation of a zirconium oxide coating with a large membrane pore size, a small number of pores and a high hardness, but if the voltage is too high, the membrane layer is prone to local breakdown and the bonding strength decreases. The longer the micro-arc oxidation treatment time, the denser the membrane layer, but the roughness also increases.
[0051] Step 2, the alloy with a porous calcium-stabilized tetragonal zirconia coating on the surface obtained in step 1 is placed in a high-temperature and high-pressure reactor containing a sodium hydroxide solution with a pH of 8-12 for a hydrothermal reaction at a temperature of 60-140°C for 0.5-5h. After cooling, the sample is taken out, rinsed with deionized water and dried. The first hydrothermal reaction is activated by high-temperature heat, so that the calcium and phosphorus ions in the outermost layer of the porous calcium-stabilized tetragonal ZrO2 coating containing Ca and P obtained by micro-arc oxidation in step 1 react with the alkaline solution to form HA crystal nuclei on the surface of the ZrO2 coating. The sample that has undergone the first hydrothermal reaction is placed in a high-temperature and high-pressure reactor containing a calcium and phosphorus mixed solution for a second hydrothermal reaction at a temperature of 60-140°C for 10-48h. The second hydrothermal reaction provides sufficient calcium and phosphorus elements in the hydrothermal solution, and further grows on the crystal nuclei generated by the first hydrothermal reaction to obtain a bioactive coating HA nanorod array uniformly grown on the surface of the porous calcium-stabilized tetragonal zirconia. Among them, the calcium-phosphorus mixed solution is composed of 0.2-0.5 mol / L sodium calcium ethylenediaminetetraacetate (EDTA-Ca) and 0.1-0.6 mol / L sodium dihydrogen phosphate, the solvent is deionized water, and the pH of the solution is adjusted to 8-11 with sodium hydroxide. As the hydrothermal time increases, the average diameter and length of the nanorod-shaped HA formed on the micro-arc oxidation ZrO2 coating in step one gradually increase. The hydrothermal temperature needs to be within a certain range. If the hydrothermal temperature is low, it cannot provide sufficient power for HA growth, and the obtained HA nanorods are thinner. When the hydrothermal temperature is too high, the HA nanorods are unevenly distributed and the spacing increases. The hydrothermal solution needs to be an alkaline solution, but if the pH is too high, HA tends to be generated in the hydrothermal solution and cannot grow on the coating surface.
[0052] In step 1 of the present invention, the Zr-2.5Nb alloy is polished with 400, 800, and 1500 mesh sandpapers in sequence, and then ultrasonically cleaned with acetone, deionized water, and ethanol for 10-20 minutes in sequence, and then dried in an oven at 60° C. for half an hour for use (the following embodiments will not be repeated).
[0053] The surface coating obtained in steps 1 and 2 of the present invention is rinsed with deionized water, dried in an oven at 60° C. for half an hour and then used for later use.
[0054] Embodiment 1:
[0055] Step 1: With a Zr-2.5Nb alloy with a diameter of 30 mm as the anode and stainless steel as the cathode, a micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus using a pulse power constant voltage mode to generate a porous calcium-stabilized tetragonal zirconium oxide coating on the surface of the alloy, rinse with deionized water, and dry in an oven at 60°C for half an hour for use. The electrolyte is composed of 0.03 mol / L of ethylenediaminetetraacetic acid calcium sodium (EDTA-Ca), 0.02 mol / L of sodium dihydrogen phosphate, and 0.125 mol / L of sodium hydroxide. The solvent is deionized water, and the electrolyte temperature is maintained at 15°C. The voltage of the pulse power supply is 450V, the frequency is 100Hz, the duty cycle is 26%, and the micro-arc oxidation treatment time is 5min.
[0056] See SEM photos of the surface and cross-section micromorphology of ZrO2 coatings obtained by micro-arc oxidation. Figure 1a , Figure 2 It can be seen that its surface is a uniform porous structure with a pore size of about 2-5μm. The thickness of the zirconium oxide coating is about 10μm, and it is closely integrated with the Zr-2.5Nb matrix interface. Figure 1b The ZrO2 coating is composed of four elements: Zr, O, Ca, and P. The atomic content of Ca is about 13.87%, and the atomic content of P is about 7.50%.
[0057] XRD spectrum reference Figure 3 From the XRD peak, we can know that the main phase is tetragonal zirconia. This is because Ca 2+ It is a strong stabilizer of the tetragonal phase. It enters the crystal lattice to form a substitutional solid solution, which can quickly cool to avoid eutectoid decomposition, so that the high-temperature tetragonal zirconia can be retained at room temperature. By utilizing the phase transformation of tetragonal zirconia under stress induction, the fracture toughness of the material can be improved. It is calculated that the grain size of tetragonal zirconia is about 20-30nm.
[0058] Step 2, the alloy of the surface porous calcium-stabilized tetragonal zirconia coating obtained in step 1 is placed in a reactor containing a sodium hydroxide solution with a pH of 12 for a hydrothermal reaction at a temperature of 90°C for 2 hours. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use. The sample that has undergone a hydrothermal reaction is placed in a reactor containing a calcium and phosphorus mixed solution for a secondary hydrothermal reaction at a temperature of 120°C for 24 hours to obtain a bioactive coating HA nanorod array uniformly grown on a porous calcium-stabilized tetragonal zirconia coating. Among them, the calcium-phosphorus mixed solution is composed of 0.25 mol / L sodium calcium sodium ethylenediaminetetraacetate (EDTA-Ca) and 0.25 mol / L sodium dihydrogen phosphate, the solvent is deionized water, and the pH of the solution is adjusted to 9 with sodium hydroxide. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use.
[0059] Surface micromorphology of calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method SEM Figure 4a It can be seen that the surface is a uniform nanorod-like structure with good crystallization. Figure 4e It can be seen that it is a hexagonal column with a diameter of about 69nm, a spacing of about 73nm, a height of about 636nm, and is nearly perpendicular to the surface of the porous structure. Figure 4b The ZrO2-HA nanorod coating is composed of four elements: Zr, O, Ca, and P. The atomic content of Ca is about 17.43%, and the atomic content of P is about 11.57%. The calcium and phosphorus content of the sample is further increased by the hydrothermal method. Figure 4c It can be seen that the zirconium alloy substrate, zirconium oxide coating and HA nanorod array are well bonded. Figure 4d It can be seen that HA is a nanorod array. The EDX line scan on the right shows that the Ca and P contents in the HA nanorod layer are slightly higher than those in the zirconia coating. In the vicinity of the zirconia coating and the zirconium substrate, the Ca and P content rapidly decreases to 0, while the Zr content rapidly increases. At room temperature, zirconia usually exists in a monoclinic phase (m-ZrO2), but through solid solution Ca 2+ , which can form tetragonal zirconium oxide (t-ZrO2) that is stable at room temperature. Figure 5 From the XRD peak, it can be seen that compared with the ZrO2 coating obtained by micro-arc oxidation, the hydroxyapatite phase is increased in the phase. At the same time, the tetragonal zirconia will inevitably transform into the monoclinic zirconia under heating and water vapor.
[0060] Contact Angle Reference Figure 6a The contact angles of water droplets on Zr-2.5Nb matrix, ZrO2 coating obtained after MAO (micro-arc oxidation), and ZrO2+HA nanorod coating obtained after MAO+HT (hydrothermal) were 59.82±3.46°, 34.94±2.68°, and 5.5±0.63°, respectively, indicating that HA nanorods can significantly improve the hydrophilicity on zirconia, which is beneficial to promote osteoblast adhesion and improve bone integration ability.
[0061] Figure 6b , Figure 6c and Figure 6dThe roughness of the coating was measured by atomic force microscopy. After micro-arc oxidation treatment, a rough and porous zirconium oxide coating was formed on the surface of the zirconium alloy. The average surface roughness of the coating was 539.67±38.44nm, which was significantly increased compared with the surface roughness of the polished Zr-2.5Nb substrate of 5.25±0.17nm. After hydrothermal growth of HA nanorods, the average surface roughness of the coating increased slightly to 652.33±17.25nm. The improvement of the surface roughness of the coating can improve osteogenesis and enhance the adhesion between the implant and the host bone.
[0062] The scratch method is usually used to test the adhesion of the coating. During the test, the scratch tester starts to load automatically, and the indenter will continue to move on the sample surface. As the load applied to the sample increases, the coating on the sample surface will break and peel off, and an acoustic emission signal will be generated. The acoustic emission signal measured in the experiment is recorded and combined with the scratch and peeling position under the scanning electron microscope to determine the critical load of the coating surface. Figure 7a and Figure 7b , it is calculated that the bonding force between the calcium-stabilized tetragonal zirconia obtained by micro-arc oxidation and the substrate is 25.4N, and the bonding force between the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal method and the calcium-stabilized tetragonal zirconia is 24.8N. ① is the surface without peeling. It can be seen from the EDS image that the contents of Ca, P, O, and Zr are related to Figure 4b The element contents of the two are similar. The surface at ② is after peeling. It can be seen from the EDS image that it is still composed of four elements: Ca, P, O, and Zr. Compared with ①, the Zr content is significantly increased, while the Ca, P, and O contents are all reduced. The peeling position still contains the four elements of Ca, P, O, and Zr, indicating that the peeling position is ZrO2 obtained by micro-arc oxidation, rather than Zr-2.5Nb matrix. It can be seen that the obtained bonding force is the cohesive bonding force of the coating.
[0063] Embodiment 2:
[0064] Step 1: With a Zr-2.5Nb alloy with a diameter of 20 mm as the anode and stainless steel as the cathode, a micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus in a pulse power constant voltage mode to generate a porous calcium-stabilized tetragonal zirconium oxide coating on the surface of the alloy, rinse with deionized water, and dry in an oven at 60°C for half an hour for use. The electrolyte is composed of 0.01 mol / L of ethylenediaminetetraacetic acid calcium sodium (EDTA-Ca), 0.02 mol / L of sodium dihydrogen phosphate, and 0.125 mol / L of sodium hydroxide. The solvent is deionized water, and the electrolyte temperature is maintained at 25°C. The voltage of the pulse power supply is 450V, the frequency is 100Hz, the duty cycle is 26%, and the micro-arc oxidation treatment time is 5min.
[0065] Step 2, the alloy with the surface porous calcium-stabilized tetragonal zirconia coating obtained in step 1 is placed in a reactor containing a sodium hydroxide solution with a pH of 12 for a hydrothermal reaction at a temperature of 90°C for 2 hours. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use. The sample that has undergone a hydrothermal reaction is placed in a reactor containing a calcium and phosphorus mixed solution for a secondary hydrothermal reaction at a temperature of 120°C for 24 hours to obtain a bioactive HA nanorod array uniformly grown on a porous calcium-stabilized tetragonal zirconia coating. Among them, the calcium-phosphorus mixed solution is composed of 0.25 mol / L sodium calcium sodium ethylenediaminetetraacetate (EDTA-Ca) and 0.25 mol / L sodium dihydrogen phosphate, the solvent is deionized water, and the pH of the solution is adjusted to 9 with sodium hydroxide. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use.
[0066] The surface micromorphology SEM photos of the porous calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation and the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal methods are shown in Figure 8a Figure 8b and Figure 8c , combined with the following table, it can be seen that Example 2 has similar EDS element composition and XRD phase composition as Example 1.
[0067] element Ca P Zr O sum At% 6.93 2.11 28.26 62.70 100
[0068] Embodiment 3:
[0069] Step 1: With a Zr-2.5Nb alloy with a diameter of 15 mm as the anode and stainless steel as the cathode, a micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus in a pulse power constant voltage mode to generate a porous calcium-stabilized tetragonal zirconium oxide coating on the surface of the alloy, rinse with deionized water, and dry in an oven at 60°C for half an hour for use. The electrolyte is composed of 0.02 mol / L of ethylenediaminetetraacetic acid calcium sodium (EDTA-Ca), 0.02 mol / L of sodium dihydrogen phosphate, and 0.125 mol / L of sodium hydroxide. The solvent is deionized water, and the electrolyte temperature is maintained at 20°C. The voltage of the pulse power supply is 450V, the frequency is 100Hz, the duty cycle is 26%, and the micro-arc oxidation treatment time is 5min.
[0070] Step 2, the alloy with the surface porous calcium-stabilized tetragonal zirconia coating obtained in step 1 is placed in a reactor containing a sodium hydroxide solution with a pH of 12 for a hydrothermal reaction at a temperature of 90°C for 2 hours. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use. The sample that has undergone a hydrothermal reaction is placed in a reactor containing a calcium and phosphorus mixed solution for a secondary hydrothermal reaction at a temperature of 120°C for 24 hours to obtain a bioactive HA nanorod array uniformly grown on a porous calcium-stabilized tetragonal zirconia coating. Among them, the calcium-phosphorus mixed solution is composed of 0.25 mol / L sodium calcium sodium ethylenediaminetetraacetate (EDTA-Ca) and 0.25 mol / L sodium dihydrogen phosphate, the solvent is deionized water, and the pH of the solution is adjusted to 9 with sodium hydroxide. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use.
[0071] The surface micromorphology SEM photos of the porous calcium-stabilized tetragonal zirconia coating obtained by micro-arc oxidation and the calcium-stabilized tetragonal zirconia-HA bioactive coating obtained by micro-arc oxidation and hydrothermal methods are shown in Figure 9a , Figure 9b and Fig.9c , combined with the following table, it can be seen that Example 3 has similar EDS element composition and XRD phase composition as Example 1.
[0072] element Ca P Zr O sum At% 12.51 5.98 21.75 59.76 100
[0073] Embodiment 4:
[0074] Step 1: With a Zr-2.5Nb alloy with a diameter of 25 mm as the anode and stainless steel as the cathode, a micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus in a pulse power constant voltage mode to generate a porous calcium-stabilized tetragonal zirconium oxide coating on the surface of the alloy, rinse with deionized water, and dry in an oven at 60°C for half an hour for use. The electrolyte is composed of 0.1 mol / L calcium sodium ethylenediaminetetraacetate (EDTA-Ca), 0.2 mol / L sodium dihydrogen phosphate, and 0.125 mol / L sodium hydroxide. The solvent is deionized water, and the electrolyte temperature is maintained at 10°C. The voltage of the pulse power supply is 470V, the frequency is 100Hz, the duty cycle is 26%, and the micro-arc oxidation treatment time is 3min.
[0075] Step 2, the alloy with the surface porous calcium-stabilized tetragonal zirconia coating obtained in step 1 is placed in a reactor containing a sodium hydroxide solution with a pH of 10 for a hydrothermal reaction at a temperature of 90°C for 1h. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use. The sample that has undergone a hydrothermal reaction is placed in a reactor containing a calcium and phosphorus mixed solution for a secondary hydrothermal reaction at a temperature of 90°C for 24h to obtain a bioactive HA nanorod array uniformly grown on a porous calcium-stabilized tetragonal zirconia coating. Among them, the calcium-phosphorus mixed solution is composed of 0.25mol / L sodium calcium sodium ethylenediaminetetraacetate (EDTA-Ca) and 0.25mol / L sodium dihydrogen phosphate, the solvent is deionized water, and the pH of the solution is adjusted to 10 with sodium hydroxide. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use.
[0076] Example 4 has similar surface micromorphology, EDS element composition and XRD phase composition to Example 1.
[0077] Embodiment 5:
[0078] Step 1: With a Zr-2.5Nb alloy with a diameter of 40 mm as the anode and stainless steel as the cathode, a micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus in a pulse power constant voltage mode to generate a porous calcium-stabilized tetragonal zirconium oxide coating on the surface of the alloy, rinse with deionized water, and dry in an oven at 60°C for half an hour for use. The electrolyte is composed of 0.03 mol / L of ethylenediaminetetraacetic acid calcium sodium (EDTA-Ca), 0.02 mol / L of sodium dihydrogen phosphate, and 0.125 mol / L of sodium hydroxide. The solvent is deionized water, and the electrolyte temperature is maintained at 18°C. The voltage of the pulse power supply is 380V, the frequency is 200Hz, the duty cycle is 26%, and the micro-arc oxidation treatment time is 10min.
[0079] Step 2, the alloy with the surface porous calcium-stabilized tetragonal zirconia coating obtained in step 1 is placed in a reactor containing a sodium hydroxide solution with a pH of 12 for a hydrothermal reaction at a temperature of 140°C for 2 hours. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use. The sample that has undergone a hydrothermal reaction is placed in a reactor containing a calcium and phosphorus mixed solution for a secondary hydrothermal reaction at a temperature of 100°C for 48 hours to obtain a bioactive HA nanorod array uniformly grown on a porous calcium-stabilized tetragonal zirconia coating. Among them, the calcium-phosphorus mixed solution is composed of 0.45 mol / L sodium calcium sodium ethylenediaminetetraacetate (EDTA-Ca) and 0.45 mol / L sodium dihydrogen phosphate, the solvent is deionized water, and the pH of the solution is adjusted to 9 with sodium hydroxide. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use.
[0080] Example 5 has similar surface micromorphology, EDS element composition and XRD phase composition to Example 1.
[0081] Embodiment 6:
[0082] Step 1: With a Zr-2.5Nb alloy with a diameter of 35 mm as the anode and stainless steel as the cathode, a micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus using a pulse power constant voltage mode to generate a porous calcium-stabilized tetragonal zirconium oxide coating on the surface of the alloy, rinse with deionized water, and dry in an oven at 60°C for half an hour for use. The electrolyte is composed of 0.2 mol / L calcium sodium ethylenediaminetetraacetate (EDTA-Ca), 0.2 mol / L sodium dihydrogen phosphate, and 0.125 mol / L sodium hydroxide. The solvent is deionized water, and the electrolyte temperature is maintained at 22°C. The voltage of the pulse power supply is 300V, the frequency is 100Hz, the duty cycle is 7.5%, and the micro-arc oxidation treatment time is 30min.
[0083] Step 2, the alloy with the surface porous calcium-stabilized tetragonal zirconia coating obtained in step 1 is placed in a reactor containing a sodium hydroxide solution with a pH of 12 for a hydrothermal reaction at a temperature of 90°C for 5 hours. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use. The sample that has undergone a hydrothermal reaction is placed in a reactor containing a calcium and phosphorus mixed solution for a secondary hydrothermal reaction at a temperature of 120°C for 48 hours to obtain a bioactive HA nanorod array uniformly grown on a porous calcium-stabilized tetragonal zirconia coating. Among them, the calcium-phosphorus mixed solution is composed of 0.5 mol / L sodium calcium sodium ethylenediaminetetraacetate (EDTA-Ca) and 0.5 mol / L sodium dihydrogen phosphate, the solvent is deionized water, and the pH of the solution is adjusted to 10 with sodium hydroxide. After cooling, the sample is taken out, rinsed with deionized water, and dried in an oven at 60°C for half an hour for use.
[0084] Example 6 has similar surface micromorphology, EDS element composition and XRD phase composition to Example 1.
[0085] The double-layer structure coating prepared by the preparation process of the present invention has no discontinuous interface with the substrate, and has high bonding strength and good biological activity. The HA nanorod array design is close to the nanofiber morphology of natural bones, has a biomimetic effect, can improve the biocompatibility of Zr-2.5Nb alloy, and has important significance in the direction of zirconium alloy orthopedic implants and hard tissue repair.
Claims
1. A tetragonal zirconium oxide / HA nanoarray bioactive composite coating grown on the surface of a zirconium alloy, characterized in that: The zirconium alloy is a Zr-2.5Nb alloy, a tetragonal zirconia coating covers the surface of the zirconium alloy, the tetragonal zirconia coating is a porous calcium-stabilized tetragonal zirconia coating containing Ca and P, and the HA nanoarray bioactive coating is uniformly grown on the surface of the tetragonal zirconia coating, and the HA nanoarray bioactive coating is in the shape of a hexagonal prism.
2. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface as claimed in claim 1, characterized in that: The following steps are involved: S1, using Zr-2.5Nb alloy as anode, micro-arc oxidation reaction is carried out in an alkaline electrolyte containing calcium and phosphorus in a pulse power constant voltage mode, the voltage is 300-500V, and a tetragonal ZrO2 coating containing Ca and P porous calcium stabilized is generated on the surface of the Zr-2.5Nb alloy to obtain a composite a; S2, subjecting complex a to a first hydrothermal reaction in an alkaline solution at 60-140°C, and then subjecting it to a second hydrothermal reaction in an alkaline mixed solution containing calcium and phosphorus at 60-140°C, so that the HA nanoarray bioactive coating grows uniformly on the surface of the tetragonal zirconia coating to form a composite material, thereby completing the growth of the tetragonal zirconia / HA nanoarray bioactive composite coating on the surface of the zirconium alloy.
3. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The solvent of the alkaline electrolyte in S1 is deionized water, and the solutes are calcium sodium ethylenediaminetetraacetate, sodium dihydrogen phosphate and sodium hydroxide. The concentration of calcium sodium ethylenediaminetetraacetate is 0.01-0.2 mol / L, the concentration of sodium dihydrogen phosphate is 0.02-0.2 mol / L, and the concentration of sodium hydroxide is 0.05-0.25 mol / L.
4. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The micro-arc oxidation reaction described in S1 is carried out under the conditions of a frequency of 50-200 Hz and a duty cycle of 7.5-26%.
5. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The micro-arc oxidation reaction described in S1 is carried out at a voltage of 300-500 V for 3-30 min.
6. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The alkaline solution described in S2 is a sodium hydroxide solution with a pH of 8-12.
7. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The first hydrothermal reaction described in S2 is carried out at 60-140°C for 0.5-5h.
8. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The second hydrothermal reaction described in S2 is carried out at 60-140°C for 10-48h.
9. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The solvent of the alkaline mixed solution described in S2 is deionized water, and the solutes are calcium sodium ethylenediaminetetraacetate, sodium dihydrogen phosphate and sodium hydroxide. The concentration of calcium sodium ethylenediaminetetraacetate is 0.2-0.5 mol / L, the concentration of sodium dihydrogen phosphate is 0.1-0.6 mol / L, and the concentration of sodium hydroxide makes the pH of the alkaline mixed solution 8-11.
10. The method for growing a tetragonal zirconium oxide / HA nanoarray bioactive composite coating on a zirconium alloy surface according to claim 2, characterized in that: The Zr-2.5Nb alloy described in S1 is obtained by the following process: the initial Zr-2.5Nb alloy is polished with 400-mesh sandpaper, 800-mesh sandpaper and 1500-mesh sandpaper in sequence, then ultrasonically cleaned with acetone, deionized water and ethanol for 10-20 minutes respectively, and finally dried at 55-65°C for 25-35 minutes; The complex a obtained in S1 is rinsed with deionized water, then dried at 55-65°C for 25-35 minutes, and then subjected to the first hydrothermal reaction. After the first hydrothermal reaction, the complex b obtained is rinsed with deionized water, then dried at 55-65°C for 25-35 minutes, and then subjected to the second hydrothermal reaction. The composite material is rinsed with deionized water, then dried at 55-65°C for 25-35 minutes, thereby completing the growth of a tetragonal zirconia / HA nanoarray bioactive composite coating on the surface of the zirconium alloy.
Citation Information
Patent Citations
Preparation method for HA nano-tube bioactive coating layer
CN107130279A
Preparation method of HA nano array bioactive coating
CN110438484A
Shuttle transfer system
KR1020250106949A